Quadriceps strength symmetry does not modify gait mechanics after anterior cruciate ligament reconstruction, rehabilitation, and return-to-sport training - Arhos, E. K.; Capin, J. J.; Buchanan, T. S.; Snyder-Mackler, L. (The American Journal of Sports Medicine, 2021)
Background: After anterior cruciate ligament (ACL) reconstruction (ACLR), biomechanical asymmetries during gait are highly prevalent, persistent, and linked to posttraumatic knee osteoarthritis. Quadriceps strength is an important clinical measure associated with preoperative gait asymmetries and postoperative function and is a primary criterion for return-to-sport clearance. Evidence relating symmetry in quadriceps strength with gait biomechanics is limited to preoperative and early rehabilitation time points before return-to-sport training.